Wheat F-box Protein TaFBA1 Positively Regulates Plant Drought Tolerance but Negatively Regulates Stomatal Closure - An, Jie; Li, Qinxue; Yang, Junjiao; Zhang, Guangqiang; Zhao, Zhongxian; Wu, Yunzhen; Wang, Yong; Wang, Wei (Frontiers in Plant Science, 2019)
The phytohormone abscisic acid (ABA) regulates plant growth and development, as well as responses to various stresses such as salt and drought. The wheat TaFBA1 gene, which encodes an F-box protein, was previously identified in our lab by homologous cloning. We previously found that TaFBA1 expression was induced by ABA and drought stress. In this study, Wild-type (WT), TaFBA1 over-expressing (OEs), TaFBA1 homologous gene mutants, and TaFBA1 recovery (Rs) Arabidopsis plants were used. We found that the germination rate, the cotyledon greening rate, the root length, and the photosynthetic performance of TaFBA1 OE plants were better than those of WT under drought and ABA conditions, but mutant plants showed the opposite trend, and overexpression of TaFBA1 in mutants can recovery their phenotype. In addition, TaFBA1 was found to be a negative regulator of ABA-induced stoma movement; mRNA transcription of certain ABA signaling related genes was lower in TaFBA1 OE plants than in WT plants following ABA treatment. Further, we found that TaFBA1 can interact with RCAR1 (an ABA receptor) and ABI5. BiFC assay showed that TaFBA1 may interact with RCAR1 in the plasma membrane. In addition, accumulation of ROS and MDA in TaFBA1 OE plants was lower than that in WT plants after ABA and drought treatments. Based on these results, we suggest that TaFBA1-regulated ABA-insensitivity may be dependent on regulating ABA-mediated gene expression through interacting with RCAR1 and ABI5. Increased antioxidant competence and decreased ROS accumulation may be an important mechanism that underlies improved drought tolerance in TaFBA1 OE plants.